COSMETIC CONSUMPTION PATTERN AMONG MALE COLLEGE STUDENTS: A CLUSTER ANALYTIC SEGMENTATION APPROACH - K.G.SANKARANARAYANAN AND NANDAKUMAR MEKOTH (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE & MANAGEMENT, 2014)
Usage of cosmetics among young men is on the increase. Personal care product manufacturers are targeting their products, promotion and distribution increasingly to this growing market. It will be useful to segment this market and understand the behaviour of each segment with respect to consumer behaviour variables. This research work conducted among college male students by surveying a sample of 80 respondents attempted to segment the market using cluster analysis using usage and benefit variables. The analysis resulted in formation of three clusters (Medium self-directed, Heavy other-directed, and Occasional non- believers) with varying characteristics. The usage and attitude of the clusters were found to differ significantly. The first cluster had medium usage with self directed attitude and medium perception of benefits. The second cluster had heavy usage with other directed attitude and high benefit perception. The third cluster had light usage with self directed attitude and low benefit perception. The clusters were found to differ in place of residence with medium self directed and occasional non believers having higher percentage of rural students while heavy other directed had higher representation of urban students. While brand preference for body spray was found to vary by cluster brand preference for face wash, shaving cream and face cream was not varying by cluster. Other variables of interest to marketer like outlet choice, reasons for use and considerations in buying were not found to vary by cluster membership. Surprisingly enough, skin type was not varying by cluster. Interestingly, heavy other directed were the lowest spenders with average spending of Rs. 684 and medium self directed were medium spenders with Rs. 950 and occasional non believers were the highest spenders with Rs. 2221 per month. The findings are of theoretical and practical significance.